Epidemiology, pathogenesis and management of atrial fibrillation in athletes - a narrative review - Jan Zabierowski; Anna Tomasiewicz; Maciej Pachana; Piotr Kukuła; Marcin Piersiak; Hubert Sawczuk; Julia Marschollek; Maciej Ziomek (Quality in Sport)
Background:Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting millions worldwide. While moderate physical activity is known to reduce AF risk, endurance athletes, particularly males, appear to have a higher prevalence of AF. The relationship between physical activity and AF follows a U-shaped curve, where both sedentary lifestyles and extreme-levels of physical activity increase the risk. Understanding the pathophysiology, risk factors, and management of AF in athletes is crucial for optimizing both cardiovascular health and athletic performance.